Pengaruh pelatihan terhadap kinerja karyawan di holiday inn resort bali benoa - Juliastuti, Ni Made; Suarka, Fanny Maharani; Sari, Ni Putu Ratna (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 2 (2021): Vol.5,No.2,2021DO - 10.24843/JKH.2021.v05.i02.p11, 2022)
Training is an effort to improve the skills, knowledge and performance of employees technically and can help employees to achieve certain skills and abilities in order to succeed in doing their jobs so that employees work according to existing operational standards of the company in order to improve employee performance. A complaint states that employee performance needs to be considered, so training is needed at the Holiday Inn Resort Bali Benoa. The purpose of this study was to determine the types of training at Holiday Inn Resort Bali Benoa and the effect of training on employee performance at Holiday Inn Resort Bali Benoa. Data collection techniques using observation, interviews, questionnaires, documentation and literature studies. The questionnaire was distributed to 100 respondents who were Holiday Inn Resort Bali Benoa employees with a proportional random sampling technique. The analytical method is descriptive qualitative and quantitative descriptive which includes the Likert scale, validity test, reliability test, simple linear regression analysis, correlation analysis, analysis of determination and t-test. The results of this study explain that the types of training conducted at the Holiday Inn Resort Bali Benoa are in-house training, inviting outside trainers and education and training programs. The results also showed a positive and significant effect of training on the performance of Holiday Inn Resort Bali Benoa employees. Training contributed 61.5% to employee performance, while the remaining 38.5% was influenced by other factors.   Keywords : Training, Employee Performance, Holiday Inn Resort Bali Benoa.